EFFECTIVENESS OF PRODUCTIVITY MEASURES ON PERFORMANCE AND PROFITABILITY OF SELECTED BANKS IN INDIA - Satish, Dr. Kattamuri; Jyothi, Dr. B. Rama (The journal of contemporary issues in business and government, 2022)
Productivity is one of the important measures which helps for growth and development of economy of the country. The productivity plays a crucial part in organizational achievement of excellence which is essential for dynamic society. Optimum productivity of a company depends on coordination between all inputs that yield maximum profitability with minimum effort. Hence the present study focuses on an objective to identify and compare the factors influencing the Productivity as well as profitability Performance of select Public and Private sector banks in India. The sample consists of 20 Banks which were operating in India. The study period considered for the study is ten years from 2011-2012 to 2020- 2021. The methodology which is used in the present study is Correlation analysis which helps to know the relationship between the select variables and Regression analysis is used to analyse the impact of select independent variables such as Sales Per employee, value added per employee, Profit before tax per employee, employee cost to sales and employee cost to value added on dependent variables like Return on Assets, return on Equity and Value added per fixed assets. Further Independent sample test is used to assess the relationship between Productivity and Performance measures of select Public and Private sector Banks in India. Thus, the results from correlation analysis indicate that almost all the independent variables except Sales per employee and employee cost to sales have significant relationship with dependant variables in both Public sector and private sector banks. The Regression result shows that Sales per employee is having significant negative impact on Return on Assets, return on equity and Value added per fixed assets. Independent samples test reveals that the Private sector banks are showing superior performance than Public sector banks.